The Code of the City of Staunton, Virginia 115 (1910). - (:unkn) unknown (My University, 1910)
All persons are forbidden to enter or leave the park except by the gateways; to climb or walk upon any of the walls or fence, to turn cattle, horses, goats or swine into the park; to carry firearms, or to throw stones or other missiles within it; to cut, break, or in any way injure or deface the trees, benches, shrubs, plants, turf, or any of the buildings, fences, bridges, or other constructions upon the park; or to converse with, or in any way hinder those engaged in its construction.
Keywords: CARRY - CERTAIN PUBLIC PLACES